Stan wojenny dlaczego-- - Jaruzelski, W. (Wojciech); Jaworski, Marek; Lozinski, Wlodzimierz (Warszawa : BGW, 1992)
A first person account by Jaruzelski on the reason behind the imposition of Martial Law in Poland in December 1981.
Includes index.
Keywords: Jaruzelski, W; Poland -- Politics and government -- 1980-1989.